The role of shared decision-making in shaping intent to access services for adolescents in protective custody. Issue 1 (2nd January 2019) - Beal, Sarah J.; Wingrove, Twila; Nause, Katie; Lipstein, Ellen; Mathieu, Stephane; Greiner, Mary V.
ABSTRACT: For adolescents in protective custody (e.g. foster care), decisions about living arrangements, education, and long-term planning are frequently made outside the courtroom, where involvement in decision-making has been less studied. During in-person interviews with 151 adolescents who were aged 16–20 and had been in child welfare protective custody for at least 12 months, perceived and desired amount of involvement in a recent decision was assessed. Data were coded and analysed to identify discrepancies in young people's perceptions of desired and actual levels of involvement. Results indicate that while the majority of adolescents (96%) are participating in decision-making, they generally desire more involvement in decisions made (64%). Only 7% of youth reported that their level of personal involvement and the involvement of others matched what they desired. The most common individuals identified in a decision made were child protection workers, legal professionals, and caregivers or family members. These findings enhance the existing literature by highlighting the unique issues related to giving young people in protective custody a voice, and provide an empirical foundation for guiding policies around who to involve in every-day decisions made for young people preparing for emancipation.